2019
DOI: 10.1590/s1677-5538.ibju.2018.0469
|View full text |Cite
|
Sign up to set email alerts
|

Role of native Thiol, total Thiol and dynamic Disulphide in diagnosis of patient with prostate cancer and prostatitis

Abstract: Background:Our study investigates whether Native Thiol, Total Thiol and disulphide levels measured in serum of patients with prostate cancer and prostatitis and of healthy subjects, have any role in differential diagnosis.Materials and Methods:Patients followed up for histopathologically verified diagnosis of prostate cancer and prostatitis in 2016-2017 at the Medicalpark Gaziantep Hospital Urology Clinic were included in the study. Native Thiol (NT), Total Thiol (TT), Dynamic Disulphide (DD) levels in serum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…GSH is converted to its dimer GSSG after reducing the target molecules. Therefore, the GSH/GSSG ratio indicates the oxidative state [ 44 ]. Moreover, thiol-disulphide balance plays an important role in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…GSH is converted to its dimer GSSG after reducing the target molecules. Therefore, the GSH/GSSG ratio indicates the oxidative state [ 44 ]. Moreover, thiol-disulphide balance plays an important role in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that reveal the effects of oxidative stress on chronic prostatitis, and oxidative stress markers have been identified in the urine and genital secretions of patients with prostatitis [10][11][12][13]. Studies have been conducted to explore the relationship between oxidative stress and prostate cancer, BPH and prostate inflammation [14]. Normal oxidative stress markers such as nitric oxide synthases and malonyl dialaldehyde are still in use today.…”
Section: Discussionmentioning
confidence: 99%
“…However, thiol levels can be influenced by a multitude of factors and are not diseasespecific. In addition, the studies discussed in this review have been performed in highly selected patients and control groups, without various comorbidities that influence systemic thiol levels [8,22]. This might overestimate the influence of thiols on the prognosis, as results are not generalizable to the general population of patients.…”
Section: Conclusion and General Discussionmentioning
confidence: 99%
“…Five studies reported on the thiol redox status in patients with prostate cancer [8,17,19,21,22]. All, but one [21], described significantly lower levels of total thiols in patients with prostate cancer compared to healthy controls, and three described lower native thiol levels [8,17,22], but only two studies also described lower disulfide levels [8,22]. Factors that were associated with lower thiol levels in prostate cancer constituted older age, lower educational level, current or previous smoking and a higher BMI [19].…”
Section: Prostate Cancermentioning
confidence: 99%